Uncovering compound heterozygous DYSF variants in a Chinese family affected by limb-girdle muscular dystrophy type 2B - Li, Jinlan; Zhou, Jie; Ji, Chunbo; Ma, Siqing; Zhu, Jianying; Yang, Tiejun; Dong, Danyang; Ping, Yang (Frontiers in Genetics, 2025)
This case concerns a Chinese female patient who was referred to our clinic having complained of weakness in her lower limbs. Following a series of diagnostic procedures, including electrophysiology, muscle biopsy and genetic analysis, the patient was diagnosed with limb-girdle muscular dystrophy type 2B (LGMD2B). Genetic testing revealed compound heterozygous mutations in the DYSF gene, specifically the missense mutation c.6313G>A (p.Ala2105Thr). Another variant, c.4444del (p.Glu1482Serfs*43), is a frameshift mutation. This case provides further confirmation of the LGMD2B diagnosis. It also identifies novel compound heterozygous DYSF mutations. These findings have significant implications for the diagnosis and research of genetic diseases, the management of at-risk individuals and the development of new therapies.